Effects of drug involvement on long-term users’ family members - Santana, Cleiton José; Oliveira, Magda Lúcia Felix de (Rev Rene, 2017)
Objective: to analyze the effects of drugs on the families of users included in sentinel events. Methods: an exploratory study with epidemiological investigation of 30 cases of hospitalized patients with a diagnosis of physical trauma associated with drug use (sentinel events). Results: there was a predominance of males, with an average of 40.1 years, low schooling and unemployed. Most had used drugs on average for 20.8 years and were in families with addictive behavior. The most commonly used drug was alcohol, and traumas were due to traffic accidents, falls and aggression (73.4%). Conclusion: drug abuse determined aggressiveness in the family context, previous trauma, illicit maneuvers for buying drugs, and home use of drugs, thus reinforcing social and family vulnerability.